Assessment as Learning: How Does Peer Assessment Function in Students' Learning? - Yin, Shengkai; Chen, Fang; Chang, Hui (Frontiers in Psychology, 2022)
Peer assessment (PA) is employed as one fundamental practice of classroom-based assessment in terms of its learning-oriented and formative nature. The exercise of peer assessment has multiple and additional benefits for student learning. However, research into the learning processes in peer assessment is scarce both in theory and in practice, making it difficult to evaluate and pinpoint its value as a tool in assessment as learning (AaL). This study focuses both on the learning process and outcome through assessment activities. We set out with three goals in mind: (1) to examine students' assessment performance in context, (2) to evaluate its impact on student progress, and (3) to illuminate teachers on organizing assessment activities. Three specific research questions are answered in this study: (1) How do student raters perform in the process of PA in an advanced English class? (2) To what extent do assessment activities influence the students' speaking ability? (3) What are students' perceptions of PA regarding its benefits and caveats? A total of 29 undergraduate students participated in two assessment activities on argumentative speaking. Many-Facet Rasch Model analysis was conducted to measure the rater effects both at the group level and the individual level. Bias/interaction analyses were performed to diagnose rater behavior in different contexts including the rating session, speaking session, and peer assessment vs. self-assessment. Questionnaire and semi-structured interview data were also collected to explore factors and strategies that could interfere with PA as AaL. Results show that students exhibited stable rating behavior and made progress in argumentative speaking in all dimensions, including delivery, organization, and language use. They are more stringent with themselves than with peers although there is one rare case with a bias against peers. Participants acknowledged the benefits of PA but also shared reasonable concerns in practice. This study validated the feasibility and the effectiveness of PA for student learning. Discussion on findings and guidelines for effective implementation of PA as AaL are provided.